Genome-wide identification and validation of tomato-encoded sRNA as the cross-species antifungal factors targeting the virulence genes of Botrytis cinerea - Wu, Fangli; Huang, Yani; Jiang, Wenqin; Jin, Weibo (Frontiers in Plant Science, 2023)
Recent evidence shows that small RNAs are transferred from a species to another through cross-species transmission and exhibit biological activities in the receptor. In this study, we focused on tomato-derived sRNAs play a role of defense against Botrytis cinerea. A total of 21 B.cinerea-induced sRNAs with high abundance were identified as the cross-kingdom regulator candidates by using sRNA-seq data. Among them, three sRNAs containing a miRNA (miR396a-5p) and two siRNA (siR3 and siR14) were selected for experimental validation and bioassay analysis. qRT-PCR confirmed that all of these 3 sRNAs were induced in tomato leaves by B. cinerea infection. Correspondingly, 4 virulence genes of B. cinerea respectively targeted by these 3 sRNAs were down-regulated, suggesting these 3 tomato-encoded sRNAs might be induced by B. cinerea infection and regulate the expression of the coding genes in B. cinerea. Exogenic RNA-induced gene silences analysis revealed that all of these 3 cross-species sRNAs could inhibit the virulence and spore gemination of B. cinerea. The coding genes of B. cinerea targeted by these sRNAs were also down-regulated, suggesting these B. cinerea-induced tomato sRNAs could inhibit the virulence of B. cinerea infection through targeting the virulence factors. In addition, the virulence inhibition by double strand sRNA was more effective than that by single strand sRNA. The inhibition efficiency of sRNA against B. cinerea increased with the increase of its concentration. Our findings provide new evidence into the coevolution of pathogens and host plants, as well as new directions for the use of plant-derived sRNAs to control pathogens.